Wear and blanking performance of an AlCrN PVD coated punch. - Çöl, M.; Kir, D.; Erişir, Erişir (Фізико-хімічна механіка матеріалів, 2012)
Blanking of sheet steels is one of the most frequently used processes in the manufacture industry. During blanking processes, the wear of punch occurs due to the cycled contact of opposite surfaces. Therefore, the punch is exposed to high stresses and requires high resistance against wear. When worn tools are used, the tool surface directly affects the quality of sheet products and causes some surface defects. PVD coating of punch with a surface layer of improved hardness and low friction may reduce wear. The aim of this study is to characterize tool wear of AlCrN coated punch used for sheet steel blanking. The worn punch surfaces were examined by scanning electron microscopy. Results showed that wear take place due to abrasion, adhesion, and delamination along sliding flank surfaces. Edge rounding and fracture of cutting edges were also observed. After blanking tests, the tool wear volume of punches and burr height of blanked parts were also measured. The wear volumes were determined by means of profile measurements of the worn punch carried out after completion of a large amount of blanked parts. Штампування листів сталі – один із найвідоміших процесів у виробництві, за якого штамп зношується через циклічний контакт протилежних поверхонь. Він зазнає впливу високих напружень і тому повинен володіти високою зносотривкістю. Під час використання зношеного штампа поверхня інструмента впливає на якість листових виробів та спричиняє поверхневі дефекти. Покриви на штампі, отримані за допомогою PVD, завдяки високій твердості та слабкому тертю, можуть зменшити зношування. Вивчено зношування штампа із AlCrN покривом, який використовують для штампування листів сталі. Поверхні досліджено за допомогою сканівної електронної мікроскопії. Встановлено, що зношування спричинене стиранням, адгезією та розшаруванням уздовж задньої поверхні ковзання. Визначено об’єм зносу штампа та висоту зазору штампованих частин. Штампование листов стали – один из наиболее известных процессов в производстве, когда штамп изнашивается вследствие циклического контакта противоположных поверхностей. Он пребывает под воздействием повышенных напряжений и поэтому должен обладать высокой износостойкостью. При использовании изношенного штампа поверхность инструмента влияет на качество листовых изделий и обусловливает поверхностные дефекты. Покрытия на штампе, полученные с помощью PVD, благодаря высокой твердости и меньшему трению, могут уменьшить изнашивание. Изучено изнашивание штампа с AlCrN покрытием, который используют для штампования листов стали. Поверхности исследованы с помощью сканирующей электронной микроскопии. Выявлено, что изнашивание вызвано стиранием, адгезией и расслоением вдоль задней поверхности скольжения. Определены объем износа штампа и высота зазора штампованных частей.